Tailoring the Thermal Expansion of Glass‐Ceramics by Controlled Twofold Crystallization of Li2Si2O5 and CsAlSi5O12. (18th December 2015) - Rampf, Markus; Fisch, Martin; Dittmer, Marc; Ritzberger, Christian; Schweiger, Marcel; Höland, Wolfram
Abstract : The mechanical and optical properties of Li2 Si2 O5 glass‐ceramics can be precisely controlled via the crystal morphology and content. However, the materials' coefficient of thermal expansion (CTE) depends on the fraction as well as the CTE of Li2 Si2 O5 and the residual glass phase, and therefore covers a rather narrow range between 10.2 and 11.3 *10 −6 K −1 (100–400°C). This study presents a way to tailor the CTE of lithium disilicate‐based glass‐ceramics by controlled twofold precipitation of Li2 Si2 O5 and CsAlSi5 O12 as a minor crystal phase with high CTE from homogenous Cs2 O comprising bulk base glasses. The Cs2 O content in the base glass significantly influences the nucleation and crystallization process of Li2 Si2 O5 as well as the microstructure of the glass‐ceramic materials. While the precipitation of Li2 SiO3 and Li2 Si2 O5 starts at temperatures ≤700°C, CsAlSi5 O12 forms in parallel to the enhanced formation of Li2 Si2 O5 as a result of Li2 SiO3 dissolution at crystallization temperatures >850°C. Glass‐ceramics with a CTE ranging from 11 to 13.1*10 −6 K −1 (25–500°C) and a mean biaxial strength ≥370 MPa were produced. The preliminary study of this glass system proofs the potential of twofold crystallization to control the CTE of lithium disilicate glass‐ceramics.